Monitoring truck driver working and rest hours using safety applications - Tanziila, Najmi; Djamalus, Hendra (Universitas Ahmad Dahlan, 2025)
Traffic accidents remain a major risk in commercial truck transportation, both in Indonesia and globally. A key contributing factor is driver fatigue, often resulting from excessive workloads and prolonged working hours. This study employs a descriptive case series design to evaluate the implementation of working and rest hour regulations for commercial truck drivers. Secondary data were analyzed from the third quarter of 2024 (July–September), covering three operational regions in West Java, Central Java, and East Java & Bali-Nusa Tenggara. Data were obtained from two driver safety monitoring applications used by a commercial transport operator. Initial analysis involved calculating compliance percentages across all locations in the three regions, followed by a more detailed review of three selected sites per region. Findings reveal that one region exhibited the lowest compliance with regulated working hours and demonstrated inconsistent enforcement of the required 8-hour rest period following 12 hours of work. These results highlight the need for strengthened monitoring and enforcement mechanisms to improve driver safety and reduce accident risks in the commercial transportation sector.